Comparison of Cardiovascular Changes Seen in Patients When Using Local Anesthesia with Adrenalin 1:80,000 vs Local Anesthesia with Adrenalin 1:2,00,000 - Gokul Venkateshwar; Swapna Nayan; Tejal R. Patil; Gargi Madiwale; Sarthak Dahiya; Aishwarya Nair (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this study is to compare the efficacy with the use of 2% lignocaine with adrenalin with two different concentrations and also its effect on the cardiovascular system. Materials and Methods: 100 patients were taken for this study. 68 were Male & 32 females. Extractions of mandibular bilateral teeth (Molars and Pre Molars).2% lignocaine with two different concentrations - one with 1:80000 and the other with 1:200000. Irrespective of the number of teeth extracted, inferior alveolar and lingual nerve blocks were administered (long buccal whenever necessary). Unilateral extractions were carried out in a single sitting and the other side was done on next visit. A single operator carried out all the cases. All the patients were given the same pre-operative and post-operative instructions. A total of 4ml solution was injected on each side. Results: Systolic blood pressure, pulse rate, onset of anesthesia, durationnof anesthesia and blood loss all the parameter were significant woth p value less tan 0.05. Conclusion: In accordance to our study, 2% lignocaine in 1:2,00,000 dilution of adrenaline can safely be used in minor oral surgical procedures, and is safe in hypertensive and cardiac patients as this dilution does not alter any haemodynamic parameters to a great extent.